What is Asked About Ionic on Stack Overflow (SO) ? An Empirical Study - Ezzahra Chaabi, Fatima; Alfayez, Reem (Proceedings (International Conference on Software Engineering Research, Management and Applications. Online), 2024)
Mobile applications have become ubiquitous and are essential in various aspects of life. Developing cross-platform applications represents a significant challenge in mobile application development. Ionic is a software framework that aims to simplify the creation of cross-platform applications through a unified codebase. Stack Overflow (SO) has continuously demonstrated its utility in gaining insights into various subjects within the field of software engineering. Hence, this study aims to uncover the challenges faced by developers when utilizing Ionic through an analysis of SO Ionic-related questions. We identified a set of 81,748 SO Ionic-related questions, which we further analyzed using Latent dirichlet allocation (LDA) to reveal their topics. Subsequently, we estimated the popularity and difficulty of these topics using several proxy measures. The findings revealed that SO Ionic-related questions encompass eight topics, with building errors being the most popular and Cordova plugins the most difficult. Software engineering researchers, practitioners, educators, and Ionic contributors can benefit from these findings in guiding their future endeavors related to Ionic.